Misperceiving inequality. (17th November 2017) - Gimpelson, Vladimir; Treisman, Daniel
Abstract: A vast literature suggests that economic inequality has important consequences for politics and public policy. Higher inequality is thought to increase demand for income redistribution in democracies and to discourage democratization and promote class conflict and revolution in dictatorships. Most such arguments crucially assume that ordinary people know how high inequality is, how it has been changing, and where they fit in the income distribution. Using a variety of large, cross‐national surveys, we show that, in recent years, ordinary people have had little idea about such things. What they think they know is often wrong. Widespread ignorance and misperceptions emerge robustly, regardless of data source, operationalization, and measurement method. Moreover, perceived inequality—not the actual level—correlates strongly with demand for redistribution and reported conflict between rich and poor. We suggest that most theories about political effects of inequality need to be reframed as theories about effects of perceived inequality.